The Impact of Flood Disaster on Agriculture in Tajau Landung Village - Muhammad Fahrul Razi; Sovia Husni Rahmia; Rusmaniah Rusmaniah; M. Ridha Ilhami; Syarifuddin Syarifuddun (Journal of Social Development, 2025)
The floods that hit Tajau Landung Village have had a significant impact on agricultural land and the lifestyle of the community, especially farmers who have experienced a decrease in income. The agricultural sector, with paddy rice cultivation as the main commodity, has a central role in the national economy and food security. Frequent flooding in the village poses a serious threat to farmers' livelihoods and local food security. The geographical condition of the village, which is located in a tidal lebak swamp area, makes agricultural land very vulnerable to inundation, especially during the rainy season. This research was conducted to gain in-depth knowledge on how this disaster affects agricultural productivity and the lives of farmers. This study used a qualitative method using interviews, observation and documentation. Data analysis was processed through presenting a comprehensive picture of the contribution of farmer groups in building food security and agricultural recovery efforts after the flood. The results show that annual flooding causes sub-optimal harvests, pest infestations such as rats and golden snails due to waterlogging, and increased acid content in the soil that interferes with rice growth. These direct impacts cause material losses to farmers, with average incomes declining by 50% during major floods. Overall, the high frequency of flooding not only damages crops and land, but also significantly threatens agricultural production and community food security in Tajau Landung Village.